2004
DOI: 10.1136/thx.2003.015768
|View full text |Cite
|
Sign up to set email alerts
|

Association of bronchial hyperresponsiveness and lung function with C-reactive protein (CRP): a population based study

Abstract: Background: C-reactive protein (CRP), a marker of systemic inflammation, is a powerful predictor of adverse cardiovascular events. Respiratory impairment is also associated with cardiovascular risk. Although some studies have found an inverse relationship between lung function and markers of systemic inflammation, only one study has reported a relationship between lung function and CRP levels. In contrast, little is known about the relationship between bronchial hyperresponsiveness (BHR) and systemic inflammat… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

14
117
0
1

Year Published

2007
2007
2014
2014

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 127 publications
(132 citation statements)
references
References 33 publications
14
117
0
1
Order By: Relevance
“…The temporal relationship between systemic inflammation and poor lung function is also unclear. Although several studies have explored this association [1,[10][11][12][13][14][15], each of these studies had certain limitations. Some of these studies were cross sectional in nature and unable to assess the temporal relationships [10,11].…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…The temporal relationship between systemic inflammation and poor lung function is also unclear. Although several studies have explored this association [1,[10][11][12][13][14][15], each of these studies had certain limitations. Some of these studies were cross sectional in nature and unable to assess the temporal relationships [10,11].…”
mentioning
confidence: 99%
“…Although several studies have explored this association [1,[10][11][12][13][14][15], each of these studies had certain limitations. Some of these studies were cross sectional in nature and unable to assess the temporal relationships [10,11]. Longitudinal studies have found that lung function decline was associated with raised levels of CRP at follow-up, but found little or no evidence that high levels of CRP predicted a subsequent decline in lung function.…”
mentioning
confidence: 99%
“…However, there is also evidence that systemic inflammation plays a primary role in the development (and possibly progression) of these diseases [15,16]. This conclusion comes from numerous prospective studies showing that markers of systemic inflammation, notably elevated interleukin (IL)-6 or C-reactive protein (CRP), are consistently associated with an increased risk of COPD and lung cancer in both population and cohort studies [17][18][19][20][21][22][23][24]. In several prospective studies, elevated markers of systemic inflammation have been repeatedly associated with a decline in lung function in young adults [17][18][19] and COPD in adults [20][21][22].…”
Section: Systemic Inflammation In the Copd-lung Cancer Linkmentioning
confidence: 96%
“…This conclusion comes from numerous prospective studies showing that markers of systemic inflammation, notably elevated interleukin (IL)-6 or C-reactive protein (CRP), are consistently associated with an increased risk of COPD and lung cancer in both population and cohort studies [17][18][19][20][21][22][23][24]. In several prospective studies, elevated markers of systemic inflammation have been repeatedly associated with a decline in lung function in young adults [17][18][19] and COPD in adults [20][21][22]. Similarly, in numerous prospective studies of cancer, elevated systemic markers have been associated with the development of lung cancer 5-15 years later [23][24][25][26][27].…”
Section: Systemic Inflammation In the Copd-lung Cancer Linkmentioning
confidence: 99%
See 1 more Smart Citation